SAINS DAN TEKNOLOGI DALAM AL-QUR’AN DAN IMPLIKASINYA DALAM PEMBELAJARAN - Jamal Fakhry (Ta'dib: Jurnal Pendidikan Islam, 2010)
Islam deeply appreciate science and technology. The inspiration of science and technology can be found in many of Qur’anic verses. At least, there are four of science principles in Qur’an. Among of them are: istikhlaf, equilibrium, and taskhir principles. The concept of science and technology in Qur’an is also applicable and relevant to be applicated in learning process at Islamic education institution. But, there is still a problem in it, i.e. the problem of educational dichotomy. The problem can be solved by integration project in education. It can be elaborated in three issues: 1) curriculum integration, 2) learning integration, and 3) science integration (islamization of sciences).